Planning process for an operational management platform for a public transport - Ferreira, J. C.; Marcelo, A.; Basto-Fernandes, V.; Martins, A. L. (International Journal of Management and Applied Science, 2018)
This work addresses the planning process of a public passenger transport operator, including the generation of schedules and services for vehicles and drivers, in the framework of a previously agreed service. This problem will be studied in the context of all stages of the planning process: parameterization, preparation, production of performance indicators and the generation of results for different operational scenarios.